2013
DOI: 10.1177/1753425913491789
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidumstimulates NK cell cytotoxicity by inducing NKG2D/NCR activation and secretion of perforin and granulysin

Abstract: Ganoderma lucidum (G. lucidum) is a medicinal mushroom long used in Asia as a folk remedy to promote health and longevity. Recent studies indicate that G. lucidum activates NK cells, but the molecular mechanism underlying this effect has not been studied so far. To address this question, we prepared a water extract of G. lucidum and examined its effect on NK cells. We observed that G. lucidum treatment increases NK cell cytotoxicity by stimulating secretion of perforin and granulysin. The mechanism of activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Mice were housed in groups of three or four animals per cage, and were fed with either a standard chow diet (13.5% of energy from fat; LabDiet 5001; LabDiet, USA) or a high-fat diet (60% of energy from fat; TestDiet 58Y1; TestDiet, USA). The G. lucidum strain initially isolated and characterized at Chang Gung Biotechnology and the water extract of cultured mycelium were processed as described before 62 . Briefly, the water extract was prepared by mixing 400 g of dried G .…”
Section: Methodsmentioning
confidence: 99%
“…Mice were housed in groups of three or four animals per cage, and were fed with either a standard chow diet (13.5% of energy from fat; LabDiet 5001; LabDiet, USA) or a high-fat diet (60% of energy from fat; TestDiet 58Y1; TestDiet, USA). The G. lucidum strain initially isolated and characterized at Chang Gung Biotechnology and the water extract of cultured mycelium were processed as described before 62 . Briefly, the water extract was prepared by mixing 400 g of dried G .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, CD3 + (T lymphocytes), CD4 + (T helper cells), and CD8 + (T suppressor cells) showed increased levels. Chang et al (2014) noted that Ganoderma lucidum stimulated the secretion of perforin and granulysin, granule proteins with lytic properties that increase NK cell cytotoxicity. However, in a Cochrane review (Jin et al, 2016), researchers noted that Zhang et al (2000) found a negative impact on NK cell activity with ganoderma administration; however, this study is only available in Chinese and not available for verification.…”
Section: Bufa (Formulas and Herbs That Tonify)mentioning
confidence: 99%
“…Many traditional Chinese medicines and their active constituents, such as Ganoderma lucidum, Astragalus membranaceus, Panax ginseng and Grifola frondosa by enhancing the cytotoxic activity of NK cells play a role in anti-tumor (Chien et al, 2004;Chang et al, 2014;Zeng et al, 2012;See et al,1997;Ting et al, 2014).…”
Section: Introductionmentioning
confidence: 96%